The Use of Online Media as A Means of Marketing Communication for Msmes in Bandung - Hasim Hasim (Journal of Social Science, 2021)
The change in human mindset in marketing products departs from the rapid development of communication and information technology, and at this time the world leads to online services. This study departs from the initial observations of researchers related to MSMEs in The City of Bandung which is so much accompanied by good government attention. UMKM data recorded in the office of micro and medium enterprises cooperatives in the city of Bandung amounted to 6140 people, thus showing that the city of Bandung became the center of young business people. The number of MSMEs that are so much needed a proper and effective marketing communication so that the products offered can be in demand by consumers. Departing from some of these images this research reveals the marketing methods of MSMEs, and describes the form of marketing communication of MSMEs through online media. Based on the theme raised in this study, researchers set the research method using qualitative method with deskrptif approach. The results of this study describe that marketing methods are done online and offline, from these two methods online marketing is considered more effective because it can reach consumers widely with relatively affordable promotional costs. The form of marketing communication of MSMEs is seen based on the type of business, but in general hamir is the same as giving information about the advantages of products offered, and differences with similar products.